Hepatitis C genotype distribution in patient and blood donor samples in South Africa for the period 2008–2012. Issue 11 (21st August 2016) - Prabdial‐Sing, N.; Chirwa, T.; Thaver, J.; Smuts, H.; Vermeulen, M.; Suchard, M.; Puren, A. J.
Summary: There are limited molecular epidemiological studies of hepatitis C at a national level in South Africa. The introduction of newer treatment modalities for hepatitis C requires knowledge of the genotypes as these may have different prognostic and therapeutic implications. This retrospective study describes genotype distributions of patients attending specialist clinics and a blood donor group studied during the period 2008–2012 in South Africa. Residual samples from diagnostic viral load testing from specialist clinics in South Africa (n=941) and from the South African National Blood Service (n=294) were analysed quantitatively by real‐time PCR and genotyped using the Versant line probe assay or sequencing. Genotype 1 was predominant in blood donors (34%), whilst genotype 5a was prevalent in patients (36%). In the blood donor group, genotype 4 was detected for the first time. Genotype 2 was rare in the patient group and not detected in blood donors. Genotype 1 was the predominant genotype in the younger age groups (less than 30 years), whereas genotype 5a was found at higher proportions in the older age groups for both the patient and blood donor groups, comprising more than 60% of genotypes in those older than 50 years. Genotypes 1 and 5 were at highest proportions across all provinces compared to other genotypes. In blood donors, genotype 1 was predominant among Caucasians (43%) and genotype 5a among Blacks (54%). Such information is required for planning the impact on the health sector with regard to newly emerging therapies for hepatitis C and burden of disease.